Characterization of charging damage in plasma doping - Henke, D.; Walther, Sabine; Weemann, John; Dirnecker, Tobias; Ruf, Alexander; Beyer, Armand; Lee, K. (IEEE Proc. on Ion Implantation TEchnology-2002, 2003)
UnivIS-Import:2015-04-16:Pub.2003.tech.IE.LEB.charac

Influence of annealing temperature and measurement ambient on TFTs based on gas phase synthesized ZnO nanoparticles - Walther, Sabine; Schäfer, Stefan; Jank, M. P. M.; Thiem, H.; Peukert, Wolfgang; Frey, Lothar; Ryssel, Heiner (Microelectronic Engineering, 2010)
In this paper, we report on the applicability of gas phase synthesized ZnO nanoparticles for printed electronics. Electrical characteristics of thin film transistors with an active layer based on ZnO nanoparticle dispersions are presented. A low charge carrier mobility and a low Ion/Ioff ratio are found for the devices when measured in nitrogen atmosphere. The mobility is limited by the rough interface between semiconductor and dielectric. Additional electrical measurements in dry air reveal a dependency of the Ion/Ioff ratio on surface states of the ZnO particles. It is shown that adsorption of oxygen on ZnO nanoparticles leads to improved transistor characteristics.
Keywords: Nanoparticle; Printable electronics; Thin film transistor; Zinc oxide

Preparation and soft lithographic printing of nano-sized ITO-dispersions for the manufacture of electrodes for TFTs - Straue, Nadja; Rauscher, Martin; Walther, Sabine; Faber, Hendrik; Roosen, Andreas (Journal of Materials Science, 2009)

Properties of SiO2 and Si3 N4 as gate dielectrics for printed ZnO transistors - Walther, Sabine; Polster, Sebastian; Meyer, Benedikt; Jank, M. P. M.; Ryssel, Heiner; Frey, Lothar (Journal of Vacuum Science & Technology B, Nanotechnology and Microelectronics, 2011)
In this article, the authors report on thin film transistors based on gas phase synthesized ZnO nanoparticles using low temperature deposited silicon dioxide and silicon nitride as gate dielectrics. For bottom gate transistors, the devices using silicon nitride as gate insulator show the lowest off-current for a given induced charge and the steepest subthreshold slope. The charge carrier mobility of around 3×10-3 cm2/V s and an Ion/Ioff ratio of around 105 are almost independent of the insulator material. In a double gated thin film transistor using low stress silicon nitride as a top gate insulator, transistor parameters are extracted for the identical semiconducting layer when the bottom and top gates are used. It is shown that the extracted charge carrier mobility is not inherent for the ZnO nanoparticle layer but rather an effective value for the device under investigation.

Tuning of charge carrier density of ZnO nanoparticle films by oxygen plasma treatment - Walther, Sabine; Polster, Sebastian; Jank, M. P. M.; Thiem, H.; Ryssel, Heiner; Frey, Lothar (Advanced Powder Technology, 2011)
In this work, the charge carrier density of ZnO nanoparticle films was modified after deposition and annealing by an oxygen plasma treatment. The respective films were utilized as active layers in thin film transistors. For a discussion of the plasma–surface interaction on the molecular level, the electrical behavior of the layers was investigated which in general is highly sensitive to low level variations in defect or doping densities. A treatment with remote oxygen plasma at 400 W for 10 s led to a shift of the turn-on voltage from -12 to 4 V and a reduction of the off-current by more than two orders of magnitude. A model for the influence of oxygen species adsorbed to ZnO nanoparticle surfaces on electrical characteristics of ZnO nanoparticle thin film transistors is introduced.
Keywords: Plasma treatment; Printed electronics; TFT; ZnO